Sharing information and knowledge between Brazilian researchers - Queiroz, Fernanda Cristina Barbosa Pereira; Costa, Yan Sávio Alves da; Queiroz, Jamerson Viegas; Lima, Nilton Cesar; Silva, Christian Luiz da; Furukava, Marciano (International Journal for Innovation Education and Research, 2020)
The CIC among Brazilian researchers refers to the activity of providing information and knowledge that enables the joint work of experts for the resolution of problems and development of new ideas or theories, which usually result in joint scientific publications. Thus, the objective of this article is to elaborate a model that relates the factors that influence the diffusion of the CIC among Brazilian researchers in the modality "productivity" of CNPq, as mechanisms for generating innovations and new knowledge, measured by scientific production. As for the method, in a first moment a bibliographic research was carried out to evaluate existing models in the literature regarding the determining factors of the ICC on the capacity of innovation and generation of innovations in the HEIs, especially in the research groups. Next, the structural and measurement model was elaborated and validated using an online questionnaire for data collection, with five-point likert questions, sent to researchers in the productivity modality in research, levels SR, 2, 1A, 1B and 1C of CNPq. The questionnaire was answered by 262 researchers and the collected data were analyzed using the SEM analysis instrument based on PLS. The results found indicated that the hypotheses of the model were accepted. The results revealed that the individual characteristics of the researchers, the organizational characteristics and the technology contribute to the CIC, which in turn favors the generation of publications and promotion of knowledge. In addition, individual characteristics and publications contribute to the advancement of innovation.